(Optimal) governance of research support by "Survey Methodology" - Marek Fuchs (Rat für Sozial- und Wirtschaftsdaten (RatSWD), 2009)
Survey research is an integral element of modern social science. The infrastructure in terms of research institute, surveys, conferences and journals has greatly improved over the past 20 years and recently several initiatives have gained momentum even on a European level. This development has brought about the need for an integrated theoretical concept in order to assess and evaluate the quality of surveys and survey estimates. In our view, survey methodology is an interdisciplinary body of knowledge and expertise that describes the "science of conducting and evaluating surveys". It is a theory-driven empirical approach to assess the quality of survey research. Thus, it applies the principles of survey research to the development and assessment of this very method. Even though surveys have been conducted in a highly professional manner for decades, survey methodology offers the opportunity to use a universal theoretical approach when planning and assessing surveys and also a joint terminology. Both, the integrated theoretical concept and the joint terminology foster the professionalization of survey methods and stimulates methodological research on the improvement of survey methods. One key element of survey methodology is the total survey error framework. It shall be described in greater detail below (section 1). Afterwards we will discuss some limitations of this concept (section 2) and mechanisms ad organizational issues in order to promote the use of this concept (section 3).
Keywords: 330